Affect and Social Media: Emotion, Mediation, Anxiety and Contagion - Lahouij Mohamed Anouar (Communiquer)
This text reviews the book Affect and Social Media. Emotion, Mediation, Anxiety and Contagion (2018), edited by Tony D. Sampson, Stephen Maddison and Darren Ellis. The book seeks to introduce the concept of affects, and to question the ubiquity of the digital in our daily lives in order to analyze the disproportionate role social media have acquired in our emotional lives. It shows how digital media continuously modulates our moods and feelings.